Unraveling the Contribution of Turbulence and Bubbles to Air‐Water Gas Exchange in Running Waters. Issue 3 (24th February 2022) - Klaus, M.; Labasque, T.; Botter, G.; Durighetto, N.; Schelker, J.
Abstract: Quantifying air‐water gas exchange is critical for estimating greenhouse gas fluxes and metabolism in aquatic ecosystems. In high‐energy streams, the gas exchange rate k is poorly constrained, due to an incomplete understanding of turbulence and bubble contributions to k . We performed a flume experiment with air bubble additions to evaluate the combined effects of turbulence and bubbles on k for helium, argon, xenon, and methane. We created contrasting hydraulic conditions by varying channel slope, bed roughness, water discharge, and bubble flux. We found that k increased from 1–4 to 17–66 m d −1 with increases in turbulence and bubble flux metrics. Mechanistic models that explicitly account for these metrics, as well as gas diffusivity and solubility, agreed well with the data and indicated that bubble‐mediated gas exchange accounted for 64–93% of k . Bubble contributions increased with bubble flux but were independent of gas type, as bubbles did not equilibrate with the water. This was evident through modeled bubble life and equilibration times inferred from bubble size distributions obtained from underwater sound spectra. Sound spectral properties correlated well with turbulence and bubble flux metrics. Our results demonstrate that (a) mechanistic models can be applied to separate free surface‐ and bubble‐mediated gas exchange in running waters, (b) bubble life and equilibration times are critical for accurate scaling of k between different gases, and (c) ambient sound spectra can be used to approximate contributions of turbulence and bubbles. Plain Language Summary: Aquatic systems exchange gases with the atmosphere and this exchange is important for many fundamental ecosystem processes and the global greenhouse gas cycle. How fast gases exchange with the atmosphere is, however, difficult to determine, especially in streams and rivers where bubbles can speed up the exchange of certain gases. Here, we used experimental stream channels to create a wide range of flow conditions, and test how these conditions affect the rate at which different gases in the water exchange with the atmosphere. We found that irregular water motions and bubbles generally enhance gas exchange and that these effects can be described by physical equations of flow and bubble characteristics in similar ways as previously shown in oceans. The equations can be used to quantify the specific contribution of bubbles to gas exchange and this can be important when comparing exchange rates of different gases such as carbon dioxide and oxygen. We also find that important drivers of gas exchange can be derived from flow and bubble sound recorded by microphones. In essence, we provide new equations and field methods that will improve our understanding and ability to quantify gas exchange processes in streams and rivers. Key Points: Air–water gas exchange rates in bubbly running waters follow the same mechanistic scaling laws as in oceans Bubble life and equilibration times are critical for accurate scaling of gas exchange rates Key drivers of gas exchange correlate with ambient sound spectral signatures